Conversion of food processing wastes to biofuel using clostridia. (December 2017) - Abd-Alla, Mohamed Hemida; Zohri, Abdel-Naser Ahmed; El-Enany, Abdel-Wahab Elsadek; Ali, Shimaa Mohamed
Abstract: This study aims to demonstrate the recycling of food processing wastes as a low cost-effective substrate for acetone – butanol - ethanol (ABE) production. Potato peels and cheese whey were utilized during fermentation with eight local Clostridium strains in addition to the commercial strain, C. acetobutylicum ATCC 824 for ABE and organic acids production. From potato peels, Clostridium beijerinckii ASU10 produced the highest ABE production (17.91 g/l) representing 61.3% butanol (10.98 g/l), 33.6% acetone (6.02 g/l) and 5.1% ethanol (0.91 g/l). While, C. chauvoei ASU12 showed the highest acid production (8.15 g/l) including 5.50 and 2.61 g/l acetic and butyric acids, respectively. Use of cheese whey as fermentable substrate exhibited a substantial increase in ethanol ratio and decrease in butanol ratio compared to those produced from potato peels. Clostridium beijerinckii ASU5 produced the highest ABE concentration (7.13 g/l) representing 50.91% butanol (3.63 g/l), 35.34% acetone (2.52 g/l) and 13.74% ethanol (0.98 g/l). The highest acid production (8.00 g/l) was obtained by C. beijerinckii ASU5 representing 4.89 and 3.11 g/l for acetic and butyric acid, respectively. Supplementation of potato peels with an organic nitrogen source showed NH4 NO3 promoted ABE production more than yeast extract. In conclusion, this study introduced an ecofriendly and economical practice for utilization of food processing wastes (renewable substrates as potato peels and cheese whey) for biofuel production using various Clostridium strains. Highlights: This study introduced an ecofriendly and economical approach for biofuel production. Potato peels and cheese whey were used as low cost fermentable substrates. Clostridium beijerinckii ASU10 showed high potential for ABE production. Supplementation of NH4 NO3 to the feedstock enhanced ABE production.